BENDING OF A PILE FOUNDATION IN THE PRESENCE OF ZONES OF ELASTIC AND ELASTIC-PLASTIC LAW OF INTERACTION WITH THE SOIL ENVIRONMENT - Batirjan Mardonov; Dilfuza Ismatova; Abdulkhafiz Akhmadaliev (Journals Park Publishing, 2024)
Improving the quality and efficiency of construction on subsidence soils largely depends on the correct assessment of their properties and the choice of foundations. It is traditionally believed that when constructing on weak and subsidence soils, priority belongs to pile foundations, which are of particular importance in the construction of underground and buried structures in urban conditions, leading to the development of additional settlements of the surrounding buildings located in the zone of influence of new construction. The article proposes a method for calculating the effect of horizontal force on the grillage of a pile (single column) buried in the soil and interacting with it according to the elastic-plastic law. Bedding coefficient
Keywords: Subsidence, deepening, settlement, plastic law, development, intensity.